Acute and severe ocular manifestations of a patient with Stevens-Johnson Syndrome in RSUD Wangaya: a case report - Jelly Vianti Fransisca Oeiyano; Jessica Yolanda Hadisusanto; Lisa Berliani Tanaya; Ida Ayu Putri Kartiningsih (DiscoverSys Inc., 2022)
Background: Stevens-Johnson syndrome is a severe mucocutaneous disorder with high mortality rates and potentially life-threatening. Ocular manifestations in SJS occurred up to 81%, with manifestation ranging from conjunctiva hyperemia, cicatrizing conjunctivitis with symblepharon, corneal ulceration, corneal blisters and perforation, which can potentially lead to permanent vision loss. Case Description: A 34-year-old male patient was being consulted to ophthalmologist department with the diagnosis Stevens-Johnson syndrome, he was complaint bilateral upper and lower eyelid palpebral conjunctiva adhesion to bulbar conjunctiva. The ophthalmological examination cannot be examined due to the adhesion then the patient was performed bilateral symblepharon separation of the eyelid using blunt-tip of surgical scissors under local anesthesia. After the procedure, the visual acuity was around 3/60 for both eyes. The anterior segment examination in both eyes showed that the palpebral was edema, peeling of the skin. The conjunctiva appears to be chemosis, conjunctival injection, with mucopurulent secret in both eyes. The patient was treated with antibiotic combined with steroid eye ointment and eye drop. Conclusion: Ocular manifestations of SJS are mostly mild-moderate. However, several cases possess grave complication and may progress to vision loss. Treatment for the ocular sequelae can reduce the risk of long-term visual morbidity. Knowing the etiology along with the progression of the disease is necessary for early diagnosis and prompt treatment.